HARMONISASI KETENTUAN HUKUMAN DISIPLIN PEGAWAI ASN UNTUK MENJAMIN KEPASTIAN HUKUM - Nurmalita Ayuningtyas Harahap (Universitas Islam Kadiri, 2022)
ABSTRACT The purpose of this study is to find out the harmonization of disciplinary provisions based on the ASN Law and the Civil Servant Discipline Regulation in ensuring legal certainty. The type of this research is normative juridical research. The study was carried out using a conceptual approach and a statutory approach. This research is a library research. The results of this study are first, the existence of disharmony in the Civil Service Disciplinary Administration towards the ASN Law, among others regarding the provisions regarding respectful dismissal, the prohibition of ASN from becoming members and/or administrators of political parties. and the existence of a provision stating that all disciplinary provisions in the PP Discipline of Civil Servants apply to PPPK in the PP Discipline of Civil Servants. Second, harmonization efforts that can be carried out are of course with improvements made by officials who are authorized to make and stipulate Government Regulations related to the provisions in the Civil Service Disciplinary Regulations adjusted to the provisions in the ASN Law, among others related to the provisions regarding honorable dismissals, there is a prohibition of ASN from becoming members and/or administrators of political parties. and the existence of a provision stating that all disciplinary provisions in the PP Discipline of Civil Servants apply to PPPK in the PP Discipline of Civil Servants. Keywords: Harmonization, Discipline For ASN, Legal Certainty ABSTRACT Tujuan dalam penelitian ini adalah ingin mengetahui harmonisasi tentang ketentuan disiplin berdasarkan UU ASN dan PP Disiplin PNS dalam menjamin kepastian hukum. Adapun Jenis penelitian ini adalah penelitian yuridis normatif. Penelaahan dilakukan dengan pendekatan konseptual (conceptual approach) dan pendekatan perundang-undangan (statute approach). Penelitian ini merupakan penelitian kepustakaan (Library Research).Hasil dari penelitian ini adalah pertama, adanya disharmonisasi di PP Disiplin PNS terhadap UU ASN, antara lain tentang ketentuan tentang pemberhentian dengan hormat, adanya larangan ASN menjadi anggota dan/atau pengurus partai politik. dan adanya ketentuan yang menyatakan bahwa keseluruhan ketentuan disiplin di PP Disiplin PNS berlaku bagi PPPK di dalam PP Disiplin PNS. Kedua, Upaya harmonisasi yang dapat dilakukan tentunya dengan pembenahan yang dilakukan oleh pejabat yang berwenang membuat dan menetapkan Peraturan Pemerintah terkait dengan ketentuan yang ada di PP Disiplin PNS disesuaikan dengan ketentuan yang ada di UU ASN, antara lain berkaitan dengan adanya ketentuan tentang pemberhentian dengan hormat, adanya larangan ASN menjadi anggota dan/atau pengurus partai politik. dan adanya ketentuan yang menyatakan bahwa keseluruhan ketentuan disiplin di PP Disiplin PNS berlaku bagi PPPK di dalam PP Disiplin PNS. Kata Kunci: Harmonisasi, Disiplin ASN, Kepastian Hukum